Pencitraan Bakal Capres 2014 dalam Media Online - SUYONO SUYONO (Universitas Muhammadiyah Yogyakarta, 2014)
The year 2013 is called a political year by many observers. It is because this year KPU announces the political parties which will join 2014 General Election. This period is also used by the leaders of political parties to consolidate their organizations, and determine the candidates of legislature members or even consider the figures for 2014 presidential candidates. It is natural that the figures of presidential candidates start to emerge in the society. It can be through socialization and introduction of the Presidential candidates, either in the form of posters, billboards, or advertisements in the media and other ways. The purpose is that the figures will be immediately recognized by the people who become constituents. This study examines the role of media in society. Each mass media certainly has its own view of the upcoming 2014 presidential candidates. Keywords: Image building, 2014 Presidential Candidates, The Role of Online Media, Van Dijk’s Discourse Analysis